Safety assessment of the process PETman, based on Starlinger Decon technology, used to recycle post‐consumer PET into food contact materials - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Vittorio Silano; José Manuel Barat Baviera; Claudia Bolognesi; Andrew Chesson; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Alicja Mortensen; Gilles Rivière; Inger‐Lise Steffensen; et al. (EFSA Journal, 2019)
Abstract The EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP) assessed the safety of the recycling process PETman (EU register number RECYC163) using the Starlinger Decon technology. The input is hot washed and dried poly(ethylene terephthalate) (PET) flakes originating from collected post‐consumer PET containers, mainly bottles, with no more than 5% PET from non‐food consumer applications. They are preheated before being submitted to solid‐state polycondensation (SSP) in a continuous reactor at high temperature under vacuum and gas flow. Having examined the challenge test provided, the Panel concluded that the preheating (step 2) and the decontamination in the continuous SSP reactor (step 3) are the critical steps that determine the decontamination efficiency of the process. The operating parameters to control the performance of these critical steps are temperature, pressure, residence time and gas flow. It was demonstrated that this recycling process is able to ensure that the level of migration of potential unknown contaminants into food is below the conservatively modelled migration of 0.1 μg/kg food. Therefore, the Panel concluded that the recycled PET obtained from this process is not considered of safety concern, when used at up to 100% for the manufacture of materials and articles for contact with all types of foodstuffs for long‐term storage at room temperature, with or without hotfill. Trays made of this recycled PET are not intended to be used in microwave and conventional ovens and such use is not covered by this evaluation.